Return to Rio: Agency problems and the political economy of environmental treaties - Roger D. Congleton (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
This paper uses a political principal-agent model to analyze the process by which international environmental treaties are negotiated and ratified. To the extent that political principals hire negotiators on the basis of their negotiation skills rather than their policy preferences, negotiators will generally favor more stringent environmental regulations than their principals. Consequently, there will tend to be a greater consensus among negotiators for stringent environmental treaties than among principals. And, treaties will be greener than politically optimal. Historical and statistical evidence from the treaties negotiated at the World Summit in Rio de Janeiro is consistent with the analysis developed.
Keywords: 330; Umweltabkommen; Prinzipal-Agent-Theorie; Neue politische Ökonomie; Theorie